Effects of Intrauterine Human Chorionic Gonadotropin on Endometrial Receptivity in Intracytoplasmic Sperm Injection Cycle - Omaima Al Dosary; Huda Hussaini; Manal Al-Obaidi (Al-Anbar Medical Journal)
Background: Human chorionic gonadotropin (hCG) is one of the chief embryonic signals in primates. It modifies the uterine environment, encourages uterine receptivity, and plays a key role in embryo implantation.Objectives: To determine the impact of intrauterine infusion of hCG at day of ovum pickup on the endometrial receptivity using ultrasound measurement of endometrial thickness and sub-endometrial blood flow indices like resistance index (RI), pulsatility index (PI), and systole/diastole (S/D) ratio, and on improvement of intra-cytoplasmic sperm injection (ICSI) outcome.Material and methods: This comparative study included 90 infertile females from the High Institute of Infertility Diagnosis and Assisted Reproductive Technologies, Baghdad, Iraq. The patients were randomly classified into three groups: Group A (30 women received intrauterine insemination of 700 IU hCG); Group B (30 women received 500 IU hCG); and Group C (30 women received no intervention). Ultrasound examination and assessment of plasma hormone level on cycle days 2-3 were done for all patients like follicle stimulating hormone, luteinizing hormone, estradiol E2, prolactin, and thyroid stimulating hormone. Embryo transfer, luteal support, and serum beta-hCG on day 14 after embryo transfer were performed, and the pregnancy rate was registered.Result: Group A had significantly lower means for the RI, PI, and S/D ratio than groups B and C (P-value = 0.001, 0.002, and 0.027, respectively). Group A had a significantly higher pregnancy rate (P-value = 0.035) than group C. However, there was no significant difference between groups A and B (P-value > 0.05).  Conclusion: Infusion of 700 IU hCG can improve sub-endometrial blood flow by reducing the RI and PI. These effects will improve the pregnancy rate in patients undergoing the ICSI cycle.